ANALISIS YURIDIS PEMBENTUKAN DESA BAGAN LIMAU KECAMATAN UKUI KABUPATEN PELALAWAN BERDASARKAN PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 72 TAHUN 2005 TENTANG DESA - Budi Prasetyo; Dodi Haryono; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Before the village was expanded into the origin of the village is very important. The origin of this is the main issue of various parties, the establishment of Bagan Limau Hamlet. Proposal division Dusun Desa Bagan Bagan Limau Limau be filed by the village of Lubuk Kembang Bungo. In accordance with a map of the boundary between the village of Black Water and the village of Lubuk Kembang Bunge in 2004 made by the Government of Pelalawan and deal the two villages between Air Hitam village and the village of Lubuk Kembang Bungo, Hamlet Bagan Limau get into government territory Desa Air Hitam not Lubuk Kembang Bungo but Pelalawan Regional Regulation No. 11 of 2007 on the establishment Desa Bagan Limau. Article 3, that the village of Bagan Limau come from parts of the village of Lubuk Kembang Bungo Subdistrict Ukui. The purpose of writing this skirpsi, namely, first, to understand the formation of the village of Bagan Limau diliat of the Indonesian Government Regulation No. 72 Year 2005 on the village. Second, to determine the Establishment Legal Implications Hamlet Bagan Bagan Limau Limau into the village.Keywords: Establishment Village – Bagan Limau - Breaking Regulation Legislation